Stakeholder Perspectives on MAPS. (1st July 2022) - Sanchez, Amanda L.; Hoskins, Katelin; Pettit, Amy R.; Momplaisir, Florence; Gross, Robert; Brady, Kathleen A.; Hoffacker, Carlin; Zentgraf, Kelly; Beidas, Rinad S.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Managed problem solving (MAPS) is an evidence-based intervention that can boost HIV medication adherence and increase viral suppression, but it is not widely used in community clinics. Deploying community health workers to deliver MAPS could facilitate broader implementation, in support of the Ending the HIV Epidemic (EHE) initiative's goal of reducing new HIV infections in the US by 90% by 2030. Setting: Ryan White-funded clinics in Philadelphia, 1 of 48 US counties prioritized in the EHE. Methods: Semistructured stakeholder interviews were conducted with 13 clinics and 4 stakeholder groups: prescribing clinicians, nonprescribing clinical team members (eg, medical case managers), clinic administrators, and policymakers. Interviews were based on the Consolidated Framework for Implementation Research and investigated perceived barriers to and facilitators of MAPS delivery by community health workers. Rapid qualitative analytic techniques were used to synthesize interview data and identify key categories along an implementation pathway. Core determinants (ie, barriers and facilitators) of MAPS implementation were grouped within each category. Results: Stakeholders were receptive to CHW-delivered MAPS and offered critical information on potential implementation determinants including preferences for identification and referral of patients, and the importance of integration and communication within the care team. Conclusions: This study elucidates insights regarding barriers and facilitators to delivering an evidence-based behavioral intervention in clinics serving people with HIV (PWH) and extends a rapid qualitative approach to HIV care that rigorously incorporates stakeholder data into the development of implementation strategies. It also offers insights for national implementation efforts associated with EHE.